At Xinjian Tuvans: twenty years later - Mongush, Marina V. (The New Research of Tuva, 2012)
The article is about the international scientific expedition led by Japanese professor Y.Konagaya to Xinjiang district of the Republic of China in summer 2012. Author investigates the features of way of life and culture of Chinese Tuvans.